2021
DOI: 10.47836/pjssh.29.s3.16
|View full text |Cite
|
Sign up to set email alerts
|

English Language Speaking Anxiety, Self-Confidence and Perceived Ability among Science and Technology Undergraduate Students: A Rasch Analysis

Abstract: The purpose of this paper is to analyse English language speaking anxiety, self-confidence, and perceived ability in English oral communication among Science and Technology undergraduate students. It also aims to identify any significant differences in these constructs based on selected students’ demographic variables. The study employed the survey method with a 41-item questionnaire administered to a voluntary response sample of three hundred 3rd and 4th-year science and technology undergraduates from three M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…The findings of this study indicate that the content validity of the questionnaire used in the research was high. The Content Validity Index (CVI) value for the instrument was 0.97, which is significantly higher than the recommended cut-off value of 0.8 [3]. This demonstrates that the questionnaire adequately preserved all 27 recommended items after experts judgment.…”
Section: The Findingsmentioning
confidence: 82%
See 2 more Smart Citations
“…The findings of this study indicate that the content validity of the questionnaire used in the research was high. The Content Validity Index (CVI) value for the instrument was 0.97, which is significantly higher than the recommended cut-off value of 0.8 [3]. This demonstrates that the questionnaire adequately preserved all 27 recommended items after experts judgment.…”
Section: The Findingsmentioning
confidence: 82%
“…It is important to note that an instrument cannot be valid unless it is reliable. Wong [3] stated that a reliability coefficient exceeding 0.70 is perfectly adequate. In this study, the questionnaire demonstrated acceptable reliability, as all Cronbach's alpha coefficients exceeded 0.7 (Table 3 and Table 4).…”
Section: The Findingsmentioning
confidence: 99%
See 1 more Smart Citation